2022
DOI: 10.1177/01632787211068899
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Health-Related Quality of Life and Its Associated Factors During COVID-19 Pandemic in Jordan: A Cross-Sectional Study

Abstract: Healthcare workers worldwide have been exposed to extraordinary stress during COVID-19 pandemic. This study aimed to investigate health-related quality of life (HRQoL) level and its health and occupational associated factors among Jordanian physicians during COVID-19 pandemic. A cross-sectional design using an online survey was adopted targeting physicians at different Jordanian hospitals. The study survey included demographics, HRQoL measured by 12-item Short Form health survey (SF-12) mental and physical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 84 publications
3
7
0
Order By: Relevance
“…However, our previous studies and similar studies in the countries have revealed similar high levels of stressors influenced mental and physical health of various occupational groups in Jordan [10,[31][32][33]. These physical and mental stressors appeared to have influence when investigating medical professions' occupation groups in Jordan during the COVID-19 pandemic [9,34].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…However, our previous studies and similar studies in the countries have revealed similar high levels of stressors influenced mental and physical health of various occupational groups in Jordan [10,[31][32][33]. These physical and mental stressors appeared to have influence when investigating medical professions' occupation groups in Jordan during the COVID-19 pandemic [9,34].…”
Section: Discussionsupporting
confidence: 54%
“…The results of this study might be informative to reduce work-related stress challenging hospitalbased nurses during similar pandemics and regular circumstances [9,12,13,19]. Musculoskeletal pain challenging nurses might be managed using proper manual handling and ergonomic training and by consulting rehabilitation professionals [49,50].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…20 Moreover, it will enhance HRQoL of patients, provide effective therapeutic assistance to physicians, and alleviate the mayhem associated with notorious processes far before the emergence of the pandemic. 82 Vitamin C infusion at a high dose is expected to be one of the challenging therapies to combat inflammation and oxidative stress in a critically ill individual. Antioxidant balance is of functional relevance during critical illness because it is involved in the pathogenesis of multi-organ failures.…”
Section: Discussionmentioning
confidence: 99%